Non-contact breath sampling for sensor-based breath analysis - Mochalski, Pawel; Shuster, Gregory; Leja, Marcis; Unterkofler, Karl; Jaeschke, Carsten; Roberts, Skapars; Gasenko, Evita; Polaka, Inese; Vasiljevs, Edgars; Shani, Gidi; Mitrovics, Jan; Mayhew, Christopher A; et al. (IOP Publisher, 2019)
Breath analysis holds great promise for real-time and non-invasive medical diagnosis. Thus, there is a considerable need for simple-in-use and portable analyzers for rapid detection of breath indicators for different diseases in their early stages. Sensor technology meets all of these demands. However, miniaturized breath analyzers require adequate breath sampling methods. In this context, we propose non-contact sampling; namely the collection of breath samples by exhalation from a distance into a miniaturized collector without bringing the mouth into direct contact with the analyzing device. To evaluate this approach different breathing maneuvers have been tested in a real-time regime on a cohort of 23 volunteers using proton transfer reaction mass spectrometry. The breathing maneuvers embraced distinct depths of respiration, exhalation manners, size of the mouth opening and different sampling distances. Two inhalation modes(normal, relaxed breathing and deep breathing) and two exhalation manners(via smaller and wider lips opening)forming four sampling scenarios were selected. A sampling distance of approximately 2 cm was found to be a reasonable trade-off between sample dilution and requirement of no physical contact of the subject with the analyzer. All four scenarios exhibited comparable measurement reproducibility spread of around 10%. For normal, relaxed inspiration both dead-space and end-tidal phases of exhalation lasted approximately 1.5 s for both expiration protocols. Deep inhalation prolongs the end-tidal phase to about 3 s in the case of blowing via a small lips opening, and by 50% when the air is exhaled via a wide one. In conclusion, non-contact breath sampling can be considered as a promising alternative to the existing breath sampling methods, being relatively close to natural spontaneous breathing. --///-- This work is licensed under a CC BY 4.0 license.
Keywords: breath sampling; volatile organic compounds; PTR-MS; breath analysis; Research Subject Categories::MEDICINE